PENGUKURAN LEVEL KETINGGIAN AIR MENGGUNAKAN FIBER BRAGG GRATING (FBG) BERBASIS MODULASI INTENSITAS LASER DIODA - Setiono, Andi; Sari, Ratna Yulia (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Measurement of water level use Fiber Bragg Grating (FBG) was studied. The measurement was done by straining FBG use cantilever which connected to the cork. By straining of the FBG, grating period will have changed and further affect the transmission response of the propagated light. In this study, the water levels were measured by detect intensity of transmitted laser diode. Wavelength of laser diode and FBG Bragg wavelength were 1553.96 nm and 1554 nm, respectively. The results showed that there is a linear relationship between intensity of transmitted laser diode with the water levels. Sensitivity and resolution were 0.69 dBm/ mm and 1 mm, respectively. Keywords: Fiber bragg grating, water level sensor, modulation of laser diode intensity.